TINJAUAN KRITIS TERHADAP KEBIJAKAN HARGA GABAH DAN BERAS DI INDONESIA - Rizka Amalia Nugrahapsari; Manuntun Parulian Hutagaol (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2021)
The government intervened unhulled rice and rice price policies which requires a large budget and is faced by a trade off between protecting producers and consumers. There is also a rice trading system that has an interest in creating profits. This condition creates obstacles in achieving policy objectives. Objectives of this paper are (1) to analyze the effectiveness of unhulled rice and rice price policies and factors that affect policy effectiveness, (2) to formulate policy recommendations in minimizing side effects. Analysis using secondary data and literature review methods. Results showed that with support of other rice policies, price policy has achieved its goal of stabilizing prices and supporting economic stability. However, it is not yet effective enough to protect farmers' income, affordability of rice prices, and safeguard government rice reserves. Pricing policies need to be carried out selectively with a clear target date and be accompanied by policy instruments for farmer income and food consumption flexibility, as well as encouraging farmer independence. Farmers can be facilitated to choose profitable commodities supported by an information system, market access, credit policies, input subsidies and agricultural infrastructure such as irrigation.